Cyborgs in Latin America (2010)
From the late nineteenth century, robots and artificial humans have gathered at the periphery of Latin American cultural production. Eduardo Holmberg’s robots from his 1879 novella Horacio Kalibang o los autómatas took center stage in the work of an author who never arrived at the center of Argentina’s literary circles. A couple of decades later, Horacio Quiroga, an author whose production has an important place in the Latin American literary canon, kept his novella Hombre artificial (1909) at the edge of his own oeuvre, publishing it as a serial under a pseudonym. While writers and artists have returned to the idea of technological life in a variety of venues since then, from Ernesto Sabato’s scientific and technological paranoia (Hombre y engranajes 1951) to Julio Cortázar’s fear of a cybernetic revolution (Rayuela 1963), only recently has a consideration of corporeal identity at the encounter of the mechanical and the organic occupied a central space in Latin American culture. These earlier works presented the various robots, artificial life forms, and technophilia as harbingers of a failing civilization, of the effects of scientific hubris and the uncritical acceptance of new technologies. Holmberg’s robots were metaphors for the dangers he saw in uncontrolled immigration in nineteenth-century Argentina; Quiroga’s artificial man was a retelling of the Frankenstein story.